Severe congenital neutropenia due to jagunal homolog 1 (JAGN1) mutation: a case report and literature review - Thomas, Sanya; Guenther, Geoffrey; Rowe, Jared H.; Platt, Craig D.; Shimamura, Akiko; Levy, Ofer; Ganapathi, Lakshmi (Frontiers in Pediatrics, 2023)
Severe congenital neutropenia due to jagunal homolog 1 (JAGN1) mutation is a rare condition resulting from maturation arrest secondary to endoplasmic reticulum stress response from impaired neutrophil protein glycosylation. We report a case of a four-yearold boy who presented with a history of recurrent infections and manifestations including recurrent intracranial hemorrhage. A review of similar cases reported in the literature indicates a bleeding diathesis has not been previously described in these patients. We hypothesize this newly described association of bleeding complications in this patient with JAGN1 mutation is secondary to defective glycosylation in the normal functioning of platelets or clotting factors. Recurrent infections with intracranial hemorrhage, new focal neurologic defects, or altered mental status in a child should warrant a suspicion for this immunodeficiency for the prompt initiation of treatment and prophylaxis for life-threatening infections or trauma.